Abundance, diversity and richness of natural enemies of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), in Zambia - Chipabika, Gilson; Sohati, Philemon H.; Khamis, Fathiya Mbarak; Chikoti, Patrick C.; Copeland, Robert; Ombura, Levi; Kachapulula, Paul W.; Tonga, Tamara K.; Niassy, Saliou; Sevgan, Subramanian (Frontiers in Insect Science, 2023)
The fall armyworm (FAW), Spodoptera frugiperda, an invasive pest originating from the Americas is a serious pest threatening cereal production and food security in Zambia. We studied the prevalence and abundance of natural enemies of FAW in three Agroecological regions (AERs I, II, and III) to identify those that could potentially serve as bio-control agents. Sampling of FAW parasitoids and predators was done along trunk roads at intervals of 10 km. Molecular sequence analysis and morphological characterization were used to identify natural enemies. Over 11 species of FAW natural enemies, including egg, egg-larval, and larval parasitoids, and predators, were identified in Zambia. The mean number of natural enemies and species richness was higher in AER I and IIa. Consequently, egg parasitism was highest in those two regions, at 24.5% and 12.2%, respectively. Larvae parasitism was highest in AER I (4.8%) and AER III (1.9), although no significant differences were observed. The most abundant and widely distributed parasitoid was Drino sp. (Diptera: Tachinidae), while Rhynocoris segmentarius (Germar) (Hemiptera: Reduviidae) and Belanogaster sp. (Hymenoptera: Vespidae) were the most prevalent predators.Our study reveals the presence of two natural enemies belonging to the genus Tiphia and Micromeriella, uncommon to FAW. Significant differences in the number of parasitoids were observed in polycropping, with the highest recovery of 12 ± 10% from maize + cowpeas + pumpkin and watermelon mixed cropping. The higher the rainfall, the lower the number of natural enemies recorded. Variations in rainfall patterns which affect FAW availability, cropping systems and between the three AERs may explain natural enemies' species diversity in Zambia. The information provided in this study can aid the development of a national biological control programme for its sustainable management.